Visible-light driven O2-to-H2O2 synchronized activation of peroxymonosulfate in Z-scheme photocatalytic fuel cell for wastewater purification with power generation - Wei, Ling-Wei; Liu, Shou-Heng; Nguyen, Van-Can; Zheng, Meng-Wei; Wang, Hong Paul (Applied catalysis. B, Environmental, 2025)
Antibiotics are recognized as emerging contaminants with non-biodegradation, complex structures, and abundant chemical energy, which are difficult to treat and recover energy through traditional wastewater treatment processes. A Z-scheme photocatalytic fuel cell (PFC) system, comprising C3N5 and CuO/Cu2O dual-photoelectrodes, has been developed for simultaneous power generation and degradation of antibiotics, such as berberine hydrochloride (BH). Especially, the C3N5 with its suitable energy potential for peroxymonosulfate (PMS) activation is synchronized with CuO/Cu2O, resulting in enhancing the performance of PFC system. Moreover, the interaction between PMS and Cu(I)/Cu(II) active sites on the photocathode can enhance the formation of highly reactive species (HRS) in the PFC-PMS system, thereby improving photocatalytic oxidation performance. Under visible-light illumination for 120 min, PFC-PMS system can rapidly and effectively oxidize BH (ca. 99.2 %, k = 0.0039 min−1) with simultaneous power generation (0.018 mW cm−2). This approach presents a promising approach for both water cleanup and energy reuse applications. [Display omitted] •A Z-scheme PFC system consisting of C3N5 and CuO/Cu2O photoelectrodes was prepared.•Incorporating PMS into the PFC system improves photovoltage and current density.•Synergistic PMS activation and photo-Fenton reaction in a PFC system.•A PFC system with PMS is effective and stable in oxidizing organic contaminants.•A PFC-PMS system is promising for energy self-sufficiency and water clean-up.